Cognitive impairment in stroke and multiple sclerosis - Belcher, Andrew (2021)
Background: Due to the world’s ever-growing and ageing population, dementia and cognitive impairments are major global health and socioeconomic burdens. Stroke is a leading cause of acquired cognitive impairment and dementia. Multiple sclerosis (MS) although less common than stroke, also causes cognitive impairment and in rare cases overt dementia. The risk factors for cognitive decline are still not fully understood and there is currently no recommended intervention for preventing cognitive decline. Therefore, we must determine which risk factors are associated with cognitive impairment and which interventions can help to delay or prevent the onset of cognitive impairment, to reduce the number of people who suffer from cognitive decline.